Thymus-specific serine protease contributes to the diversification of the functional endogenous CD4 T cell receptor repertoire - Viret, Christophe (The Rockefeller University Press, 2011)
Thymus-specific serine protease (TSSP) is a novel protease that may contribute to the generation of the peptide repertoire presented by MHC class II molecules in the thymus. Although TSSP deficiency has no quantitative impact on the development of CD4 T cells expressing a polyclonal T cell receptor (TCR) repertoire, the development of CD4 T cells expressing the OTII and Marilyn transgenic TCRs is impaired in TSSP-deficient mice. In this study, we assess the role of TSSP in shaping the functional endogenous polyclonal CD4 T cell repertoire by analyzing the response of TSSP-deficient mice to several protein antigens (Ags). Although TSSP-deficient mice responded normally to most of the Ags tested, they responded poorly to hen egg lysozyme (HEL). The impaired CD4 T cell response of TSSP-deficient mice to HEL correlated with significant alteration of the dominant TCR-β chain repertoire expressed by HEL-specific CD4 T cells, suggesting that TSSP is necessary for the intrathymic development of cells expressing these TCRs. Thus, TSSP contributes to the diversification of the functional endogenous CD4 T cell TCR repertoire in the thymus.